Heat transfer performance of supercritical pressure CO2 in a non-uniformly heated horizontal tube. (July 2020) - Zhang, Haiyan; Guo, Jiangfeng; Cui, Xinying; Huai, Xiulan
Highlights: Non-uniformity of the heat flux is disadvantageous to the heat transfer generally. Bulk heat transfer depends greatly on the heat transfer in top wall of horizontal tube. Heat transfer shows the best when heat focuses on bottom side for one-side heating conditions. The dimensionless number Se/Re could predict the buoyancy effect with accuracy. Abstract: The convective heat transfer performance of supercritical pressure CO2 in a horizontal tube under three wall heat flux conditions was numerically investigated. More complex heat transfer characteristics under non-uniform heating conditions than that with uniform heat flux were observed. The more non-uniform the heat flux is in the circumferential direction, the worse heat transfer performance the CO2 has under most circumstances, except for relatively small or extremely high Reynolds number Re conditions. The heat transfer in most regions of the horizontal tube is enhanced, and the bulk heat transfer performance depends on the heat transfer in the top region of the tube mainly. For one-side heating conditions, it is better to place the heat source as closer as possible to the bottom of the tube for larger heat transfer coefficient, especially under relatively high heat flux conditions. When other conditions are the same, improving the Re shrinks the discrepancies of the heat transfer performance among tubes with different sides heated, which also indicates the weakening of the buoyancy effect. The ratio of the secondary flow number to the Reynolds number Se/Re could give good predictions for the buoyancy effect on the heat transfer performance in horizontal tubes with non-uniform heat flux.